2001
DOI: 10.1182/blood.v98.12.3212
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of cyclosporine modulation of drug resistance in patients with poor-risk acute myeloid leukemia: a Southwest Oncology Group study

Abstract: Cyclosporine A (CsA) inhibits P-glycoprotein (Pgp)-mediated cellular export of anthracyclines at clinically achievable concentrations. This randomized controlled trial was performed to test the benefit of CsA addition to treatment with cytarabine and daunorubicin (DNR) in patients with poor-risk acute myeloid leukemia (AML). A total of 226 patients were randomly assigned to sequential treatment with cytarabine and infusional DNR with or without intravenous CsA. Remitting patients received one course of consoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
234
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(245 citation statements)
references
References 46 publications
2
234
0
7
Order By: Relevance
“…5,16,22,23 Our CSA regimen was based on data previously published by the SWOG on the use of CSA as an MDR modifier in patients with AML. 11 The CSA levels were not measured. Future studies of gemtuzumab -based regimens might incorporate different CSA schedules and/or CSA level monitoring, although the currently reported data would not indicate that any increase in clinically significant hepatotoxicity FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16,22,23 Our CSA regimen was based on data previously published by the SWOG on the use of CSA as an MDR modifier in patients with AML. 11 The CSA levels were not measured. Future studies of gemtuzumab -based regimens might incorporate different CSA schedules and/or CSA level monitoring, although the currently reported data would not indicate that any increase in clinically significant hepatotoxicity FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose (16 mg/kg daily) CSA has been reported by the Southwestern Oncology Group (SWOG) to prolong significantly the duration of survival and disease-free survival in high-risk patients with AML. 11 We conducted a Phase II study of a regimen combining gemtuzumab (Mylotarg) with fludarabine, ara-C, and CSA as a potential MDR modifier (MFAC) in patients with newly diagnosed AML, RAEB, or RAEBT.…”
mentioning
confidence: 99%
“…36 Patients who were randomized to receive cyclosporine A had a slightly higher CR rate (40% vs. 33%; P ϭ 0.14) but a significantly better recurrence free rate (34% vs. 9% at 2 years; P ϭ 0.031) and overall survival rate (22% vs. 12%; P ϭ 0.046). 36 The cyclosporine effect was apparent in both MDR1 positive and MDR1 negative patients but was more significant in MDR1 positive patients (median survival, 12 months vs. 4 months). The steady-state daunorubicin serum concentrations were higher for cyclosporine-treated patients, possibly due to inhibition of hepatic metabolism of daunorubicin.…”
Section: Cyclosporine Amentioning
confidence: 96%
“…The steady-state daunorubicin serum concentrations were higher for cyclosporine-treated patients, possibly due to inhibition of hepatic metabolism of daunorubicin. 36 …”
Section: Cyclosporine Amentioning
confidence: 99%
“…Nevertheless, the discovery of new agents to inhibit P-gp is still ongoing, building on encouraging in vitro studies and individual clinical trials such as the Southwest Oncology Group (SWOG 9126) study that showed a strong benefit of the use of the P-gp inhibitor cyclosporine A (CSA) in patients with relapsed or refractory AML [98] . To date, three generations of P-gp inhibitors can be distinguished.…”
Section: Overcoming P-gp Resistancementioning
confidence: 99%